PERBANDINGAN PENGARUH PROMOTION MIX TERHADAP KEPUTUSAN PENGGUNAAN DIGITAL WALLET PADA E-MARKETPLACE TOKOPEDIA DAN SHOPEE - I Gede Wisnu Satria Chandra Putra; Rachel Wulan Nirmalasari Wijaya; Devina Tasya Noverin (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This research was conducted to find effective strategies that influence decisions on using digital wallets on e-marketplaces. In this case, the authors compare the influence of the promotion mix factor carried out by the Tokopedia and Shopee marketplaces to see which promotional strategies are effective for driving decisions on using digital wallets. This research was conducted by using statistical testing methods on the data from the questionnaire collected from 155 respondents. As a result, it was found that both Tokopedia and Shopee both had a promotion mix that had a significant effect on the use of digital wallet services. It's just that when compared, Shopee's promotion mix is ​​more effective than Tokopedia’s because they excel in two aspects, namely sales promotion and direct marketing. Meanwhile, Tokopedia only excels in the advertising aspect. Keywords: decision of use, digital wallet, e-marketplace, financial technology, promotion mix.